Investigation of the influence of plasma spray sealing coatings on the effect of sealing the TV2 - 117A turbojet engine compressor - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2014)
This research shows the effect of the application of soft seals deposited by the atmospheric plasma spraying - APS process on the parts of the TV2-117A turbojet engine compressor. Western plasma spray technology and materials were applied for the first time on the parts of the compressor.. The aim was to replace the existing sealant with a new class of materials in order to increase the sealing effect and provide air flow under the highest pressure through the compressor. Soft seals are formed as duplex systems consisting of the bonding underlayer based on NiCrAl and NiAl coatings and top sealing layer coatings based on Ni - 15% graphite, Ni - 25% graphite and AlSi - polyester. This paper presents the parameters for depositing the coatings on the compressor parts as well as the mechanical and microstructural characteristics of the coatings produced with the optimal deposition parameters. The mechanical properties of the coatings were assessed by testing the microhardness of the bonding layers using the HV0.3 method and the macrohardness of the sealing layers using the HR15W method. The tensile bond strength of the duplex coatings system was investigated bytensile testing. The microstructures of the coating layers were evaluated on an optical microscope - OM. The analysis of the microstructure of the deposited layers was performed in accordance with the Pratt & Whitney and TURBOMECA standards. Coating wear was determined from the change in the dimensions of the sealing surfaces before and after testing. The dimensions were measured in the coordinate measuring machine MAUSER ML 28. This paper presents the mean value of wear in milimeters and compares it with the values of the allowed tolerance in the compressor machined parts. The sealing effect of the compressor partswas tested on a TV2-117A engine at a test station and by flight tests on an Mi-8 (HT-40) helicopter. The tests have shown that the new system of sealing coatings increases the degree of efficiency of the compressor by 10% while reducing fuel consumption by 8%.